Unpacking Youth Unemployment in Latin America - Cunningham, Wendy (2012)
High youth unemployment rates may be a signal of difficult labor market entry for youth or may reflect high churning. The European and United States literature finds the latter conclusion while the Latin American literature suggests the former. This paper uses panel data to examine whether Latin American youth follow OECD patterns or are, indeed, unique. By decomposing transition matrices into propensity to move and rate of separation matrices and estimating duration matrices, the authors find that Latin American youth do follow the OECD trends: their high unemployment reflects high churning while their duration of unemployment is similar to that of non-youth. The paper also finds that young adults (age 19-24) have higher churning rates than youth; most churning occurs between informal wage employment, unemployment, and out-of-the labor force, even for non-poor youth; and unemployment probabilities are similar for men and women when the analysis control for greater churning by young men. The findings suggest that the "first employment" programs that have become popular in the region are not addressing the key constraints to labor market entry for young people and that more attention should be given to job matching, information, and signaling to improve the efficiency of the churning period.